Polycomb-dependent nucleolus localization of Jumonji/Jarid2 during Drosophila spermatogenesis. - Goto, M.; Toda, N.; Shimaji, K.; Suong, D.N.; Vo, N.; Kimura, H.; Yoshida, H.; Inoue, Y.H.; Yamaguchi, M. (Spermatogenesis, 2016)
Drosophila Jumonji/Jarid2 (dJmj) has been identified as a component of Polycomb repressive complex 2. However, it is suggested that dJmj has both PRC-dependent and -independent roles. Subcellular localization of dJmj during spermatogenesis is unknown. We therefore performed immunocytochemical analyses with specific antibodies to dJmj and tri-methylation at lysine 27 on histone H3 (H3K27me3). Interestingly, dJmj exclusively localizes at nucleolus in the late growth stage. Examination of the dJmj localization in various Polycomb group (PcG) mutant lines at the late growth stage allowed identification of some PcG genes, including Polycomb (Pc), to be responsible for dJmj recruitment to nucleolus. In addition, we found that size of nucleolus was decreased in some of these mutant lines. In a mutant of testis-specific TAF homolog (tTAF) that is responsible for nucleolus localization of Pc, dJmj signals were detected not only at nucleolus but also on the condensed chromatin in the late growth stage. Duolink In situ Proximity ligation assay clarified that Pc interacts with dJmj at nucleolus in the late growth stage. Furthermore, the level of H3K27me3 decreased in nuclei at this stage. Taken together, we conclude that tTAF is responsible for recruitments of dJmj to nucleolus in the late growth stage that appears to be mediated by Pc. Compartmentalization of dJmj in nucleolus together with some of PcG may be necessary to de-repress the expression of genes required to cellular growth and proliferation in the following meiotic divisions.